ANN-based model integrated in thermal-hydraulics codes: A case study of two-phase wall friction model - Nguyen , Van Thai; Nguyen , Ngoc Dat (Nuclear Science and Technology, 2026)
Accurate prediction of two-phase parameters is essential for the development, operation and safety of nuclear power plants. In this paper, the ANN-based model has been developed, implemented with PDE (Partial Differential Equation) solver in case study of two-phase frictional pressure drop prediction.